Evaluating Mission Statements from a Strategic Management Perspective: A Qualitative Case Study on JCI-Accredited Hospitals (Third Sector Social Economic Review, 2026)
The aim of this study is to determine which elements mentioned in the literature are included or excluded when formulating mission statements for healthcare institutions. The study focuses on healthcare institutions operating in Turkey that are accredited by the Joint Commission International (JCI). The research was conducted using the case study design, one of the qualitative research methods. Content analysis was used to analyze the data obtained in the research, and the mission statements were interpreted. In this study, which utilised secondary data, the mission statements of 42 healthcare institutions were obtained from their websites and examined. The analysis revealed that no institution used all nine elements accepted in the literature as essential for a mission statement. The elements most frequently used by institutions were customers, products or services, philosophy, and distinguishing features. The least frequently used elements were markets, survival, growth and profitability, concern for employees, and concern for public image. It was also observed that the mission statements used by the institutions were concentrated around a few similar elements. In line with the results obtained, it was seen that healthcare institutions in Turkey did not utilise research in the literature when determining their mission statements and did not give the subject the importance it deserved. In line with these results, recommendations were made to institutions and researchers who will conduct further studies in the final section of the study.
Keywords: Strategic Mamagement; Mission; content analysis; Healthcare Institutions.